Engineering popular support for long-ruling parties: the role of clientelism. (22nd April 2019) - Zeng, Qingjie
Abstract: In electorally contested regimes, the incumbent party often uses clientelist exchanges to stay in power long after its underlying electoral support has evaporated. Existing studies failed to examine how the role of clientelism changes with the increasing tenure of the incumbent party. Combining data from the Afrobarometer project and information about partisan turnover, this article shows that the longer a party has remained in power, the more clientelist exchanges in the form of club goods and patronage will serve to bolster popular support for the ruling party. This is mainly because lengthy party duration facilitates the politicization of bureaucracy and other state resources essential for clientelist exchanges. Understanding the evolving role of clientelism under electoral contestation has profound implications for the study of phenomena such as dominant-party rule and democratic erosion.